Budget Management Strategy for Equality Education Program at The As-Salam Community Learning Activity Center (PKBM) - Nopiati, Erti; Arafat , Yasir; Furkan, Nuril (Mudir : Jurnal Manajemen Pendidikan, 2023)
This study aims to describe the strategic management of school principals in an effort to manage the budget for implementing an equality education program at the Center for Community Learning Activities (PKBM). This type of research is qualitative research. Data collection tools using documentation, interviews, observation and literature review. Data analysis used descriptive analysis. The results showed that the not optimal budget allocation was one of the reasons for the low quality of education services, the low performance of tutors and the lack of optimal socialization of PKBM to dropouts to continue with equality education. Therefore, the As-Salam PKBM budget management strategy is planned based on priority programs. The priority program consists of (1) allocating 20% of the school budget for the welfare of tutors which is given once every three months; (2) minor repairs to learning infrastructure such as minor repairs to classrooms, repainting classrooms, repairing tables and chairs and fulfillment of learning equipment ; (3) providing a transportation budget for tutors to attend seminars and competency improvement training. The priority program-based PKBM As-Salam budget management strategy has proven to be effective in improving the quality of PKBM, especially the quality of the teaching and learning process.